2019
DOI: 10.1097/cej.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for lung cancer prevention and improved survival: a novel approach

Abstract: Diabetes mellitus has been associated with increased risk for the development of many types of cancer. Metformin, an oral medication and first-line treatment for type 2 diabetes mellitus, has been suggested to reduce cancer risk and mortality in various types of cancer. This study focuses on assessing metformin association with lung cancer as reported in the literature. Recent studies and reviews investigating metformin effects on lung cancer incidence and patient survival are critically and systematically dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…While metformin alleviates cisplatin resistance in triple-negative breast cancer by facilitating RAD51 degradation [35], it has also been reported to promote cisplatin resistance in gastric cancer through PINK1/Parkin-mediated mitophagy [36]. Recent reports suggest that metformin improves the overall survival of lung cancer patients [37,38]. Although some previous studies suggest that the antineoplastic effect of metformin is closely related to mitochondrial function [39,40], it is still unclear p32/OPA1 contributes to cisplatin resistance 41 whether metformin sensitizes NSCLC to cisplatin by regulating mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…While metformin alleviates cisplatin resistance in triple-negative breast cancer by facilitating RAD51 degradation [35], it has also been reported to promote cisplatin resistance in gastric cancer through PINK1/Parkin-mediated mitophagy [36]. Recent reports suggest that metformin improves the overall survival of lung cancer patients [37,38]. Although some previous studies suggest that the antineoplastic effect of metformin is closely related to mitochondrial function [39,40], it is still unclear p32/OPA1 contributes to cisplatin resistance 41 whether metformin sensitizes NSCLC to cisplatin by regulating mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2020 report, the incidence of lung cancer was 11.4% of all types of cancer [51]. It has been shown that metformin is also important in the prevention of lung cancer and in improving the survival of patients with lung cancer [56][57][58][59]. Many in vitro and in vivo studies indicate that metformin has a strong antitumour effect.…”
Section: Lung Cancermentioning
confidence: 99%
“…Consequently, many laboratories have tried to understand the mechanisms of action of metformin in different types of cancers, such as lung, prostate, and ovarian cancers or melanoma. The in vitro effects of metformin, alone or in combination with other drugs, have been studied in many different cancers ( 29 32 ). Moreover, numerous in vivo studies have demonstrated the efficacy of metformin in decreasing tumoral growth ( 33 , 34 ).…”
Section: Metformin Acts As An Anticancer Agentmentioning
confidence: 99%